A characteristics analysis of carbon emission based on multi-dimensional carbon emission accounting methods and structural decomposition analysis: A case study of Beijing, China - Li, QingHua; Chen, Cong (Frontiers in Earth Science, 2023)
The city’s industrial transformation leads to a large amount of carbon emissions, which poses a thorny problem for the allocation of carbon responsibilities. This study established a multi-dimension long-term carbon emission analysis model to explore the characteristic of Beijing’s embodied carbon emissions, which could calculate the production-based, consumption-based and income-based carbon emissions. Then, structural decomposition analysis was adopted to quantify the contribution of socioeconomic factors in local and imported carbon emissions. In addition, emission linkage analysis was used for revealing the long-term evolutionary trajectories of sectors. The key discovery can be summarized as follows: (i) the fluctuation trend of production-side and income-side carbon emissions in Beijing is stable and decreased by 3.53% from 2002 to 2017, while consumption-side carbon emissions increased rapidly by 795.45%. (ii) The energy sector, transportation and service industries are the important carbon emission sectors from the supply, production and consumption perspectives. (iii)Per capita consumption, production structure and consumption structure are the major contributors of carbon emissions. The study is expected to provide decision support for policymakers to reasonably formulate carbon mitigation polices and allocate carbon mitigation responsibilities from multiple perspectives, and promote the realization of the "carbon peak and carbon neutrality" strategy.